ECONOMIC LIFE IN THE KHIVA KHANATE (19TH CENTURY) (TAMADDUN NURI JURNALI, 2025)
By the 19th century, many changes had occurred in the economic life of the Khiva Khanate. During this period, the khanate's internal and external trade relations with Russia and other countries developed, resulting in changes in commodity-money relations. This article analyzes the importance of commodity-money relations in the economic life of the Khiva Khanate in the 19th century.